The Science textbook: an analysis of the relationship between mangrove ecosystem content and the STSE approach (Research, Society and Development, 2020)
The Didactic Book (LD) is an important resource to corroborate the transcription of the scientific message to the educational one. However, the teacher must pay attention to understand his locus of action and assume his responsibility as an educator in the analysis of this material. That said, and due to the importance of Scientific Literacy, we seek to analyze how issues related to science and its interaction with technology, society and environment (STSE) are presented in the Science Textbook on the theme of mangrove ecosystem. Thus, we conducted a bibliographic study with a qualitative research bias. As methodological procedures, we adapted the methodology of Vasconcelos & Souto (2003) who organized in their study some categories that allowed us to list the information about the theoretical, complementary content and visual resources of the 7th year of Science LD. As a result, we noticed that the LD presented a good synthesis of the content under study, starting to relate it to the socio-environmental problems caused by the misuse of science and technology. The text was clearly presented and its definitions presented important information containing evidence of the STSE approach. However, some adjustments can be made in the next editions so that you can better discuss and consequently facilitate the involvement of students in classroom debates. Thus, the LD under study was evaluated as good, when we look at the mangrove issue.